Half a slice of bread and butter (big book) - Ferguson, Virginia (Nelson Australia South Melbourne, 1994)
"Half a Slice of Bread and Butter" is a whimsical children's story that explores themes of sharing, kindness, and the joy of simple pleasures. The narrative often follows a character who discovers the value of generosity when they encounter various friends and animals who appreciate even the smallest acts of kindness. Through charming illustrations and engaging storytelling, the book emphasizes the importance of community and the happiness that comes from giving to others. It encourages young readers to find joy in sharing what they have, no matter how little, and highlights how small gestures can create big impacts. This delightful tale is perfect for teaching children about empathy and the joy of connection.